2017
DOI: 10.1016/j.jare.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid in plants and microorganisms: Biological applications and genetics - A review

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 116 publications
(146 reference statements)
2
44
0
10
Order By: Relevance
“…Purines naturally occur in all plant foods. It was found that at least 10–15 mg of purine per 100 g of food is present in all plant foods, with most plant foods containing low or moderate concentrations [81]. The purine content in animal sources (e.g., meat and fish) generally varies from approximately 120 to over 400 mg of purine per 100 g, while the purine content in plant sources (e.g., most nonsoy legumes, grains, seeds, fruits, and other vegetables) varies from 7 to 70 mg of purine per 100 g [47].…”
Section: Purine Content Of Pbd Lifestyle May Not Be An Unavoidablementioning
confidence: 99%
“…Purines naturally occur in all plant foods. It was found that at least 10–15 mg of purine per 100 g of food is present in all plant foods, with most plant foods containing low or moderate concentrations [81]. The purine content in animal sources (e.g., meat and fish) generally varies from approximately 120 to over 400 mg of purine per 100 g, while the purine content in plant sources (e.g., most nonsoy legumes, grains, seeds, fruits, and other vegetables) varies from 7 to 70 mg of purine per 100 g [47].…”
Section: Purine Content Of Pbd Lifestyle May Not Be An Unavoidablementioning
confidence: 99%
“…Purines are part of nitrogen metabolism and include molecules such as adenine, guanine, hypoxanthine, xanthine and uric acid, among others. The purine pathway allows the recycling of the end products (glyoxylate and ammonia) to synthesize new organic compounds necessary to plant growth (Theimer and Beevers ; Nguyen ; Werner and Witte ; Hafez et al ). Moreover, purine metabolism has also been associated with the mechanism of response to environmental stresses such as drought tolerance (Stasolla et al ; Watanabe et al ; Irani and Todd ).…”
Section: Peroxisomal Uric Acid Metabolism With Dual Functions: Generamentioning
confidence: 99%
“…The second step is the conversion of hypoxanthine into xanthine and then to uric acid by the enzyme xanthine oxidoreductase (XOR) that occurs in two isoforms: the xanthine dehydrogenase (XDH) and the xanthine oxidase (XO). The third step consists of three major enzymatic reactions: (i) the oxidation of the uric acid to 5-hydroxyisourate (HIU) via a coenzymeindependent enzyme urate oxidase (UOX), also known as uricase, in a two stage-oxidation followed by hydration-in B. subtilis and B. fastidiosus (Wei et al 2016); (ii) the conversion of HIU to 5-hydroxy-2-oxo-4-ureido-2,5-dihydro-1H-imidazole-5-carboxylate (OHCU) catalyzed by the putative xanthine upregulated transthyretin-related proteins 5-hydroxyisourate hydrolase as in Escherichia coli (Urano et al 2015); and, (iii) the stereoselective decarboxylation of OHCU to the Virgilia oroboides Paraburkholderia kirstenboschensis (Steenkamp et al 2015) dextrorotatory (S)-allantoin catalyzed by the enzyme OHCU decarboxylase in, i.e., B. subtilis, E. coli, Herbaspirillum seropedicae, Klebsiella spp., and Ruegeria pomeroyi TB-90 (Matiollo et al 2009;Doniselli et al 2015;Cunliffe 2016;Hafez et al 2017). The fourth step underlies the conversion of (S)allantoin into allantoate by the enzyme (S)-allantoin amidohydrolase (allantoinase) (Werner and Witte 2011).…”
Section: Bacterial Ureide Synthesismentioning
confidence: 99%